2016
DOI: 10.4172/2167-1222.c1.003
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of compartment syndrome of the thigh secondary to quadriceps trauma and vascular injury in a soccer athlete

Abstract: INTRODUCTION: Compartment syndrome isolated to the anterior thigh is a rare complication of soccer injury. Previous reports in the English literature on sports trauma-related compartment syndrome of the thigh are vague in their description of the response of thigh musculature to blunt trauma, magnetic resonance imaging (MRI) findings of high-risk features of compartment syndrome, vascular injury in quadriceps trauma, and the role of vascular study in blunt thigh injury. CASE REPORT: We present herein the rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Yoga has proven to be an effective treatment for trauma-related illnesses and mental health disorders in a variety of populations, including veterans (Kearney, McDermott, Malte, Martinez, & Simpson, 2012; Stoller, Greuel, Cimini, Fowler, & Koomar, 2012) and victims of traumatic events (Telles, Singh, & Balkrishna, 2012). Within the correctional setting, people who are incarcerated have responded well to yoga and mindfulness-based therapies as a treatment method for trauma-related illnesses and mental health disorders (Bilderbeck, Farias, Brazil, Jakobowitz, & Wikholm, 2013; Danielly & Silverthorne, 2017; Duncombe, Komorosky, Wong-Kim, & Turner, 2005; Epstein & Gonzalez, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga has proven to be an effective treatment for trauma-related illnesses and mental health disorders in a variety of populations, including veterans (Kearney, McDermott, Malte, Martinez, & Simpson, 2012; Stoller, Greuel, Cimini, Fowler, & Koomar, 2012) and victims of traumatic events (Telles, Singh, & Balkrishna, 2012). Within the correctional setting, people who are incarcerated have responded well to yoga and mindfulness-based therapies as a treatment method for trauma-related illnesses and mental health disorders (Bilderbeck, Farias, Brazil, Jakobowitz, & Wikholm, 2013; Danielly & Silverthorne, 2017; Duncombe, Komorosky, Wong-Kim, & Turner, 2005; Epstein & Gonzalez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the Yoga Service Council published the Best Practice for Yoga in the Criminal Justice System (Horton, 2017), which serves as a resource for the development and implementation of yoga programming in jails, prisons, youth detention centers, and court-ordered programs. The Prison Yoga Project recently reported positive results, indicating that yoga intervention has reduced self-reported levels of depression and stress, and improved self-control and self-awareness for female inmates (Danielly & Silverthorne, 2017). In addition, a qualitative study of former male inmates examined the same project and reported similar results: “positive psychological impact resulting in reduced depression and anxiety, a reduction of aggressive tendencies, a reduction of physical ailments including addictive behaviors, and an increase in social participation and dedication to community” (Viorst, 2017).…”
Section: Introductionmentioning
confidence: 99%